International Financial Reporting Standards : A Practical Guide, Sixth Edition - Van Greuning, Hennie; Scott, Darrel; Terblanche, Simonet (World Bank, 2012)
An acceptable coherent framework of fundamental accounting principles is essential for preparing financial statements. The major reasons for providing the framework are to: 1) identify the essential concepts underlying the preparation and presentation of financial statements; 2) guide standard setters in developing new accounting standards and reviewing existing standards; 3) assist preparers in preparing financial statements and dealing with topics that are not covered by a specific International Financial Reporting Standard (IFRS); 4) assist auditors in forming an opinion as to whether a set of financial statements conforms with IFRS; and 5) assist users in interpreting the financial information contained in a set of financial statements that comply with IFRS. The framework sets guidelines and should not be seen as a constitution; nothing in the framework overrides any specific standard. The objective of financial statements is to provide information about the financial position (statement of financial position), performance (statement of comprehensive income), and changes in financial position (statement of cash flows) of an entity that is useful to a wide range of users in making economic decisions. Users of financial information include present and potential capital providers, employees, lenders, suppliers, customers, and the government. Financial statements also show the results of management's stewardship of the resources entrusted to it.